Efeito da inibição dos receptores canabinóides CB₁ ou CB₂ durante o período neonatal sobre o dimorfismo sexual esquelético ao longo do desenvolvimento - Kiill, Noélle Egídia Watanabe [UNESP] (2015)
The aim of the present study was to characterize the impact of brief blockade of cannabinoid CB1 or CB2 receptors during neonatal period on somatic growth and skeletal development during childhood, puberty, and adulthood in rats. Newborn Wistar rats were randomly divided into six groups, three male groups and three female groups. The treated groups received during the firsts seven days of life a subcutaneous dose of a CB1 (AM251) or CB₂ (SR144528) receptors antagonist (3 mg/kg dissolved in 50 μl of a vehicle consisting of absolute ethanol and phosphate buffered saline - PBS). Control groups received the vehicle solution in the same volume and period. Body weight was measured at 20, 40, 120 days of age and femurs were collected. The length and thickness of the femurs were measured and the areal bone mineral density (areal BMD) was determined by dual-energy X-ray absorptiometry (DEXA). Biomechanical femoral neck bending testing was used to evaluate bone breaking strength, energy to fracture, and extrinsic stiffness. Weight gain, areal BMD and bone biomechanical properties increased rapidly with respect to age in all groups. In vehicle animals, skeletal sexual dimorphism patterns were evident after puberty. However, neonatal blockade of cannabinoid CB1 and CB2 receptors promoted a transient and sex-dependent effect on the body weight and bone development throughout the life, and that neonatal inhibiting the CB1 and CB2 receptors in males promotes a biphasic effect on the acquisition of areal BMD throughout development, and increased bone fragility in males AM251 in adulthood. This study demonstrated that brief blockade of cannabinoid CB1 or CB2 receptors during neonatal period causes a long-lasting and sex-dependents modification in somatic growth and skeletal development in rats